2014
DOI: 10.1103/physrevd.90.123510
|View full text |Cite
|
Sign up to set email alerts
|

Fermi-bounce cosmology and scale-invariant power spectrum

Abstract: We develop a non-singular bouncing cosmology using a non-trivial coupling of general relativity to fermionic fields. The usual Big Bang singularity is avoided thanks to a negative energy density contribution from the fermions. Our theory is ghost-free since the fermionic operator that generates the bounce is equivalent to torsion, which has no kinetic terms. The physical system consists of standard general relativity plus a topological sector for gravity, and fermionic matter described by Dirac fields with a n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 66 publications
1
40
0
Order By: Relevance
“…Note that there is another equation of motion to describe the dynamics of cosmological perturbations, namely the perturbed equation for δφ. However, it can be shown that this equation is consistent with (421) and (424) by applying (422).…”
Section: Perturbation Analysissupporting
confidence: 65%
See 1 more Smart Citation
“…Note that there is another equation of motion to describe the dynamics of cosmological perturbations, namely the perturbed equation for δφ. However, it can be shown that this equation is consistent with (421) and (424) by applying (422).…”
Section: Perturbation Analysissupporting
confidence: 65%
“…Accompanied with this feature, it is not surprising to look for a series of nontrivial cosmological solutions that may resolve the initial singularity problem [419]. The avoidance of the Big Bang singularity by using torsion arisen from a cosmic spinor field can be found in [420][421][422][423]. Moreover, it has been known for many years that the coupling between the torsion tensor and the cosmic spinor field can lead to interesting gravitational repulsion and thus avoid curvature singularities by violating the energy condition [424][425][426][427][428][429][430].…”
Section: Cosmic Bouncementioning
confidence: 99%
“…This raises serious questions regarding stability and the fate of perturbations. A similar model, in which a topological sector is added to gravity, was proposed in which the bounce behaves in a more regular way; by adjusting the fermion number density and the mass, such a model can reproduce a scaleinvariant spectrum of perturbations [320].…”
Section: Spinors and Torsionmentioning
confidence: 99%
“…We require a bounce mechanism (see e.g. [21][22][23][24][25]) only to transition from contraction to expansion, the modes that we are observing today at CMB exits prior to the bounce. Our scenario is also very distinct from the ekpyrotic case [26] which operates at w 1 whereas we have w ≈ 1.…”
Section: Jhep08(2014)116mentioning
confidence: 99%